Shaping Power Trio of Parents' Private School Choice: Image, Attractiveness, and Experience - Huzeir Zul; Zulfadil Zulfadil; Samsir Samsir; Raden L. Garnasih; Afred Suci (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Only a few studies have concurrently investigated school image, attractiveness, and parents' past experiences at private high school within a single, emotion-based framework. This study examines the direct, indirect, and moderating relationships among these variables in shaping private high school choice in Indonesia. Employing the Hayes PROCESS Macro on data from 270 parents, analysis revealed that school image is a powerful predictor of parental school choice, operating both directly and indirectly via school attractiveness. Prior private high school experience significantly leveraged the parents' ratings of image, attractiveness, and school choice, and magnified the impact of both image and attractiveness on the final school choice. This study provides two primary contributions: First, it significantly advances the literature on emotion-based school choice by demonstrating the strong interplay between image and attractiveness. Second, it establishes prior experience as a critical moderator, indicating that the emotional drivers of choice are fundamentally different for experienced parents, offering a new insight for school management and marketing strategies that seek to leverage parental background.